Ethnic-racial relations and public schools: issues for psychology - Feldmann, Mariana; Guzzo, Raquel Souza Lobo (Revista de Psicología, 2021)
This article summarises the results of a master’s thesis built in the context of Living Space, Action and Reflection (ECOAR), an extension project of psychology to prevent violence in public schools. Recognizing the importance of Laws 10,645 and 11,645 (Insertion of Afro-Brazilian, African, and indigenous history and culture in the school curriculum), the research aimed to identify in one of the project’s schools, how the two laws are applied and to investigate how racism it is present in everyday relationships. Based on research-action-participation, the authors used as sources of information: 1) Pedagogical Political Project; 2) City Hall website and the Memory and Identity Program; 3) Mapping of students; 4) Field Diaries. From the constructive-interpretative analysis, the results showed the racism and discrimination suffered by the students; the violence experienced, naturalised and reproduced in daily life; lack of knowledge of students’ backgrounds; a lack of knowledge and difficulties in working with Laws 10.645 and 11.645 and the importance of discussing the students’ life stories. In view of the results, it was possible to outline a proposal for action to face the different forms of violence, strengthening students.